EDUCATIONAL ACTION IN A HIGH SCHOOL ON WOUNDS, DRESSINGS, AND FIRST AID: EXPERIENCE REPORT (CIPEEX, 2025)
Domestic injuries are common in everyday life, especially among adolescents, who are particularly prone to such incidents due to their active nature. During daily activities, sports, or leisure, adolescents frequently encounter various injuries, including cuts, abrasions, burns, and bruises. Understanding basic first aid and wound care techniques is essential to minimizing damage and ensuring their safety and well-being. Considering this, a health education initiative was carried out by second-year medical students from Universidade Evangélica de Goiás in October 2023, targeting high school students in a rural school in Goiás. The main objective of the project was to document the experiences and outcomes of a workshop on wound care, dressings, and first aid, which was conducted as part of a broader university outreach project aimed at improving adolescent health education. The workshop involved 220 third-year high school students and was divided into three key stages: initial evaluation, interactive teaching sessions, and assessment through a knowledge-based competition. In the first stage, students completed a pre-test to assess their initial knowledge, which was found to be limited. The second stage consisted of interactive lectures, delivered in the form of informal conversations, covering the most common domestic injuries and the appropriate first aid responses. Finally, in the third stage, students participated in a 20-question competition designed to assess the knowledge gained from the workshop and evaluate the overall effectiveness of the educational intervention. The results demonstrated a significant improvement in the students' understanding of wound care and first aid, as reflected by a decrease in errors on the post-test compared to the pre-test. This indicates that the project successfully achieved its educational objectives. Moreover, the initiative provided an enriching experience for the medical students involved, offering them an opportunity to engage with the community and enhance their teaching and communication skills. For the high school students, the workshop not only provided essential knowledge but also fostered a greater awareness of personal safety and injury prevention. The project’s success underscores the importance of continuing such health education initiatives, as they play a vital role in promoting safety and well-being among young people. Furthermore, it highlights the value of community outreach efforts in building strong, health-conscious communities, as well as the benefits of experiential learning for medical students. The effectiveness of this health education initiative in raising awareness about wound care and first aid, along with its positive impact on both high school and medical students, suggests that similar programs should be implemented more widely to promote health education in schools and communities.
Keywords: wounds; first aid; health education